PATIENTS SATISFACTION OVER IN HOUSE PHARMACY AT HOSPITALS IN COIMBATORE- TAMILNADU - SC Vetrivel; V. Krishnamoorthy; Babin Dhas. D; kumar , P.K.Jawahar (International Journal of Psychosocial Rehabilitation, 2020)
Pharmacy is an extensively used therapeutic division and many patients attend for their prescriptions. Patients arrive at the pharmacy randomly after visiting different hospital departments. Patient satisfaction depends upon service quality. To increase the likelihood that patients return to the same organization, it is important that they should be satisfied with the facilities, which decreases the possibility that they will seek similar services elsewhere. Holding on to the same customer can save time and money owing to less advertisement and promotion, creating accounts for fresh patients and explaining hospital procedures and treatment guidelines. Moreover, the cost required to attract new customer is five times more than retaining current patients. Therefore, patient satisfaction over the pharmacy is very important that is going to estimate